SUPERPOLY: MONOPOLI DI ABAD KEDUA PULUH SATU DALAM PERSPEKTIF EKONOMI ISLAM - Lukman Hamdani (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2018)
Superpoly includes 7 interrelated market spaces. Where Tesco dominates almost 30% of the Market in the UK in controlling the market. Monopoly may be in Islam and storing stock for supplies is not prohibited in Islam. because in Islam hoarding goods is not something that is wrong when hoarding goods is done purely for inventory and not to disrupt the price mechanism that occurs in the market and if the situation and condition of market structure leads to a natural monopoly economy. Keywords: Superpoly, natural monopoly, 7 spaces, Tesco, Islam